2021
DOI: 10.1111/jocd.14202
|View full text |Cite
|
Sign up to set email alerts
|

Invitro effect of pine bark extract on melanin synthesis, tyrosinase activity, production of endothelin‐1, and PPAR in cultured melanocytes exposed to Ultraviolet, Infrared, and Visible light radiation

Abstract: Background: French maritime pine bark (Pinus pinaster) extract (PBE), the registered trade name of which is Pycnogenol ® , has been studied for its depigmenting action due to its antioxidant, anti-inflammatory, and anti-melanogenic activity. However, the mechanisms through which PBE are still not fully clear.Objective: Evaluate the impact of PBE on four in vitro parameters closely associated with cutaneous pigmentation, including melanin synthesis, tyrosinase activity, endothelin-1 (ED1), and production of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Several mechanisms behind Pycnogenol ® ’s effects on skin have been elucidated ( 25 , 26 , 73 ). Clinical investigations of Pycnogenol ® supplementation for twelve weeks in women aged 55 to 68 years found increased hyaluronic acid synthase mRNA levels by 44% and collagen type 1 mRNA levels by 40% in skin biopsies ( 25 ).…”
Section: Randomized Double-blind Placebo-controlled Human Clinical St...mentioning
confidence: 99%
See 2 more Smart Citations
“…Several mechanisms behind Pycnogenol ® ’s effects on skin have been elucidated ( 25 , 26 , 73 ). Clinical investigations of Pycnogenol ® supplementation for twelve weeks in women aged 55 to 68 years found increased hyaluronic acid synthase mRNA levels by 44% and collagen type 1 mRNA levels by 40% in skin biopsies ( 25 ).…”
Section: Randomized Double-blind Placebo-controlled Human Clinical St...mentioning
confidence: 99%
“…Tyrosinase is an enzyme that activates the production of melanin, responsible for melasma in skin. In addition, Pycnogenol ® downregulated other pigmentation-related mediators in UV-light treated human melanocytes ( 73 ). Pycnogenol ® ’s ability to counteract skin hyperpigmentation was clinically validated in another study ( 26 ).…”
Section: Randomized Double-blind Placebo-controlled Human Clinical St...mentioning
confidence: 99%
See 1 more Smart Citation
“…WH130, a kind of licorice extract, inhibits melanogenesis by suppressing tyrosinase activity, particularly when heated, making it a promising option for treating various disorders of hyperpigmentation, including brown spots, ephelides, and melasma [83]. French maritime pine bark extract (PBE), with its antioxidant property, has also proved to reduce VL-induced melanin synthesis in vitro, via inhibiting tyrosinase and other pigmentationrelated mediators [84]. Furthermore, a clinical study comparing antioxidant-enriched sunscreens with tinted sunscreens showed that the former had comparable or even better efficacy than the latter [85].…”
Section: Antioxidantsmentioning
confidence: 99%